Perlindungan Hukum Terhadap Konsumen Dalam Transaksi Jual Beli Online Di Indonesia - Tubagus Yursil Gifni; Zandi Fernandi (CV. Kurnia Grup, 2026)
The development of digital technology has driven a major transformation in the trading system, especially through online buying and selling transactions (e-commerce). Ease of access, time efficiency, and wide market reach make online transactions increasingly in demand by the public. However, behind this convenience, there are various legal risks that have the potential to harm consumers, such as fraud, mismatch of goods, and misuse of personal data. This study aims to analyze the form of legal protection for consumers in online transactions in Indonesia and identify obstacles in its implementation. The research method used is normative legal research with a legislative and conceptual approach. The results of the study show that consumer protection has been regulated in various regulations such as the Consumer Protection Law and the Electronic Information and Transaction Law. However, its implementation still faces various obstacles such as low public legal literacy, weak supervision, and difficulties in law enforcement. Therefore, it is necessary to strengthen regulations, increase education, and synergy between parties to create a safe and fair digital trading system.